Cover, Table of Contents, Editorial and Reviewer Team of Jurnal Adipati Vol. 3 No. 2 2024 - Dwicahyani, Anindya Rachma (Institut Teknologi Adhi Tama Surabaya, 2024)
Supporting Documents for Jurnal ADIPATI Vol. 3 No. 2 2024 consisting of: Cover, Table of Contents, Editorial Team, Reviewer Team.